IAP triple-beam facility for simulation studies of radiation damage of materials - Baturin, V.A.; Yeryomin, S.A.; Litvinov, P.A.; Pustovoitov, S.A.; Roenko, O.Yu.; Storizhko, V.E. (Вопросы атомной науки и техники, 2022)
The project of ion irradiation facility for in-situ studies of radiation damage being developed in IAP NAS of Ukraine is presented. The platform comprises 300 kV heavy ion implanter, 50 kV collinear dual-beam light ion im-planter and 200 kV electron microscope. The optimal energies of heavy and light ion beams have been estimated. The results of computer simulation of ion transmission in the light ion implanter are presented. Представлено проект іонно-променевої платформи для in-situ досліджень радіаційних пошкоджень, що розробляється в ІПФ НАН України. Платформа містить у собі імплантер важких іонів на 300 кВ, колінеарний двохпучковий імплантер легких іонів на 50 кВ та електронний мікроскоп на 200 кВ. Оцінено оптимальні енергії пучків важких і легких іонів. Наведено результати комп’ютерного моделювання проходження іонів у імплантері легких іонів. Представлен проект ионно-лучевой платформы для in-situ исследований радиационных повреждений, который разрабатывается в ИПФ НАН Украины. Платформа включает в себя имплантер тяжелых ионов на 300 кВ, коллинеарный двухпучковый имплантер легких ионов на 50 кВ и электронный микроскоп на 200 кВ. Оценены оптимальные энергии пучков тяжелых и легких ионов. Приведены результаты компьютерного моделирования прохождения ионов в имплантере легких ионов.